2020
DOI: 10.15407/zoo2020.02.157
|View full text |Cite
|
Sign up to set email alerts
|

Variation in common blackbird (Turdus merula) nest characteristics in urban and suburban localities in Crimea

Abstract: Variation in Common Blackbird, Turdus merula (Passeriformes, Turdidae), Nest Characteristics in Urban and Suburban Localities in Crimea. Kucherenko, V. M., Ivanovskaya, A. V. -Blackbird Turdus merula is a model species for studying the impact of environmental factors on the form and structure of nests. In the middle of XX, this species began to expand its range into the artifi cial forests of the Ukrainian steppe zone. Th is expansion may have led to changes in bird behaviour, including changes in nest constru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…In terrestrial environments that are heavily modified by humans (e.g. urban areas) ANMs included cotton threads, plastic broom fibres, paper, sweet wrappers, cigarette butts, polyethylene, paper towels, wet wipes, synthetic cotton, dental floss and bottle labels [19,22,23,[69][70][71]. Urbanization is usually associated with solid waste production [33] and it is known to concentrate macroplastics [59], potentially explaining the presence of such objects.…”
Section: Discussion (A) Diversity Of Anthropogenic Nest Materialsmentioning
confidence: 99%
“…In terrestrial environments that are heavily modified by humans (e.g. urban areas) ANMs included cotton threads, plastic broom fibres, paper, sweet wrappers, cigarette butts, polyethylene, paper towels, wet wipes, synthetic cotton, dental floss and bottle labels [19,22,23,[69][70][71]. Urbanization is usually associated with solid waste production [33] and it is known to concentrate macroplastics [59], potentially explaining the presence of such objects.…”
Section: Discussion (A) Diversity Of Anthropogenic Nest Materialsmentioning
confidence: 99%
“…However, terrestrial birds may have a higher amount of ANMs incorporated in their nests [6]. Numerous terrestrial birds, particularly passerine birds, have been found to use ANMs [14,15,16,17,18,19,20,21,22,23,24,25,26,27]. These behaviors occur in a variety of families within the order Passeriformes; nevertheless, the inclusion of ANMs in wrens of the family Troglodytidae has seldom been reported [28,29].…”
mentioning
confidence: 99%